KETERLIBATAN MEREK DAN MOTIF KONSUMEN DALAM KOMUNIKASI E-WORD OF MOUTH MELALUI SOSIAL MEDIA - pramesti, diesyana ajeng; Farida, Farida; Nugroho, Wawan Satdyo (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
The objective of this research is to test and analize brand involvement ang motives consumer in the electronic-word of mouth communication engagement in social media. The kinds of electronic-word of mouth communication in social media such as writing, liking, sharing, recomending, commenting, and tweeting. The subject of this research are people who ever makes an electronic-word of mouth in social media. The object of this research are Facebook, Titter, Google+, and Alexa. The method used in the research is survey by using purposive sampling technique to 200 sosial mediaâs users in Indonesia that ever wrote a testimonial.. Datas analyze using SPSS and hypothesis testing using simple linear regression.Â  This findings shows brand involvement, product involvement, self involvement, and advice seeking Â has positive and significant effect to electronic-word of mouth communication in social media, and the other hand, other involvement has positive effect but not significant, and also need for social interaction has negative effect to the electronic-word of mouth communication in social media. In means in the research, there are 4 hypothesis supported and 2 hypothesis not supported.Â  Â